Keteladanan Guru Membentuk Kedisiplinan Beribadah Siswa: Analisis Implementasi pada Siswa Madrasah Aliyah - Rahmad Muliadi Saleh Daulay; Fatkhur Rohman (Sekolah Tinggi Agama Islam Sumatera Medan, 2023)
Students are required to be disciplined in carrying out worship, but this demand is achieved when the teacher sets an example. Because some students are reluctant to do it because the teacher also does not worship. In this regard, this study aims to analyze the implementation, supporting factors, inhibiting factors and also educator solutions in improving students' discipline in worship. This research was conducted at Madrasah Aliyah Negeri 1 Medan. The research method used is qualitative based on a descriptive approach. Fikih teacher research informants, and students. Data collection is done through observation, interviews and documentation. The results showed that the implementation of exemplary behavior was shown by the participation and assistance of teachers in reading prayers before learning, asmaul husna, tadarus Al-Qur’an, midday prayers in congregation, iftar routine sunnah and memorizing juz amma. Supporting factors are the existence of rules for implementing the midday prayers in congregation, adequate facilities and infrastructure, the existence of cooperation between educators and education staff. The inhibiting factor is the lack of understanding and awareness of students. Thus, the solution is implementing cooperation with parents of students to provide support, direction and advice regarding the discipline of carrying out worship.